Influence of gut flora on diabetes management after kidney transplantation - Luo-bei Chen; Qian Chen; Sheng Chao; Zhi-hui Yuan; Lei Jia; Yu-lin Niu (BMC Nephrology)
Abstract Post-transplant diabetes mellitus (PTDM) is a common complication following renal transplantation, and its incidence has been gradually increasing in recent years, posing a significant public health challenge. Managing PTDM is complex, as studies suggest that it involves changes in the microbial flora across multiple organs. Recent research highlights the critical role of gut flora metabolism in the development of diabetes among post-renal transplant patients. This paper reviews the alterations in gut flora observed in PTDM patients and explores how gut flora influences PTDM. These findings may offer new perspectives on targeting gut flora metabolites for the prevention and treatment of PTDM.